Refinement demands for landings H8/u8, H8/x8 and H8/z8 under standard GOST 25347-82 - Павленко, В. М.; Петко, І. В.; Хімічева, Г. І. (Eastern-European Journal of Enterprise Technologies, 2009)
The paper shows the principal possibility of replacing the GOST 25347-82 recommended "Fields tolerance and recommended landing" landings less tense, which at a reduced size tension by increasing the actual contact area, enabling the transfer of the same axial forces and torque, as shown algorithm which built table replacement